Analisis Pengaruh Remote Working terhadap Produktivitas Kerja Karyawan Generasi Z - Rahmat Da’i; Mukhzarudfa Mukhzarudfa; Ratih Kusumastuti; Wiwik Tiswiyanti (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to analyze the influence of remote working on the work productivity of Generation Z employees in the modern professional landscape. As digital natives who entered the workforce during a period of significant structural change, Generation Z exhibits unique behavioral patterns regarding workplace flexibility and autonomy. This study employs a descriptive quantitative approach to investigate the correlation between the independent variable, remote working, and the dependent variable, employee productivity. Data were collected from 50 respondents through a structured online questionnaire using a 5-point Likert scale. The samples were selected using a purposive sampling technique, focusing on young professionals born between 1997 and 2012. The data analysis was performed using simple linear regression through SPSS software to test the research hypothesis. The findings of this study indicate that remote working has a positive and significant impact on the productivity of Generation Z employees. Several key factors contributing to this increase include improved work-life balance, the elimination of stressful daily commutes, and the ability to customize a comfortable working environment. However, the study also identifies potential challenges such as digital distractions and a sense of social isolation that may arise from a lack of physical interaction. These results provide an important implication for organizations to design more adaptive human resource policies. Companies are encouraged to implement hybrid or remote models supported by robust digital collaboration tools to maintain high performance and engagement levels among the younger workforce.